Simultaneous association of different tree species with Cuba CT-115 (Pennisetum purpureum) - Sardiñas, Yurangel; Del Viento, Alejandra; Palma, J. M. (Cuban Journal of Agricultural Science, 2016)
The initial performance of the simultaneous association between high sowing density of tree species and Cuba CT-115 (Pennisetum purpureum) was characterized through a random blocks design with a factorial arrangement (4 x 5) and four replications. Factors were determined by treatments and growth from 15 to 75 days old: T1) alternate furrows of CT-115 - leucaena (Leucaena leucocephala) cv. Peru; T2) CT-115 - leucaena - CT-115 - gliricidia (Gliricidia sepium); T3) CT-115 - leucaena- CT-115 - moringa (Moringa oleifera) and T4) CT-115 -leucaena - CT-115- caesealpinia (Caesealpinia platyloba). Results showed interaction for all variables corresponding to trees. The highest number of plants m-1 (P ≤ 0.001) corresponded to moringa at 45 d from sowing (8.65) and it did not differ from leucaena at 60 d. The lowest population (P ≤ 0.001) was shown in leucaena at 15 d, without differences from gliricidia, except at 15 d. Moringa reached the highest height (P ≤ 0.001) with 104.69 cm at 75 d. The lowest height was found in leucaena at 15 d with a mean value of 3.71 cm. Leucaena showed the lowest insertion values of the first branch (P ≤ 0.001), while moringa reached 30.35 cm long. In CT-115, there were no differences among treatments, only among growth ages. It can be concluded that moringa had the best performance during the initial development stage in the simultaneous association with CT-115. Key words: silvopastoral system, forages, trees, high density